Đánh giá mức độ tác động của các yếu tố trong chính sách tự chủ nhân sự đến phát triển đội ngũ giảng viên tại trường đại học - Âu , Quang Hiếu; Nguyễn , Đức Can (Tạp chí Giáo dục, 2023)
University autonomy is considered as a strategy and solution to develop the higher education system worldwide. In Vietnam, the autonomy of higher education institutions is associated with accountability in accordance with the law, and agencies, organizations and individuals have the responsibility to respect and ensure the right to autonomy. The research results are based on survey data on 300 non-teaching staff and faculty at three universities, namely University of Education, Danang University of Education and Ho Chi Minh City University of Education from October to December, 2022. The authors identified 4 factors in the policy of university autonomy affecting the development of teaching staff with a high level of impact of these factors (3.9/5.0 points). This is an important basis for schools to develop plans and strategies to improve the effectiveness of the teaching staff at the institution.